2008
DOI: 10.1038/ng.271
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of metabolic traits in a birth cohort from a founder population

Abstract: Genome-wide association studies (GWAS) of longitudinal birth cohorts enable joint investigation of environmental and genetic influences on complex traits. We report GWAS results for nine quantitative metabolic traits (triglycerides, high-density lipoprotein, low-density lipoprotein, glucose, insulin, C-reactive protein, body mass index, and systolic and diastolic blood pressure) in the Northern Finland Birth Cohort 1966 (NFBC1966), drawn from the most genetically isolated Finnish regions. We replicate most pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
667
7
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 681 publications
(729 citation statements)
references
References 49 publications
45
667
7
1
Order By: Relevance
“…In previous studies this candidate gene has been found to explain approximately 1% of the variation of BMI in several adult populations. [36][37][38] This gene was found to be associated with BMI from 7 years of age onwards in the UK twin sample 15 and a similar finding was also observed in Danish children. 39 However, the FTO gene was able to explain only a small proportion of the genetic variation of BMI in the UK study.…”
Section: International Journal Of Obesitysupporting
confidence: 66%
See 1 more Smart Citation
“…In previous studies this candidate gene has been found to explain approximately 1% of the variation of BMI in several adult populations. [36][37][38] This gene was found to be associated with BMI from 7 years of age onwards in the UK twin sample 15 and a similar finding was also observed in Danish children. 39 However, the FTO gene was able to explain only a small proportion of the genetic variation of BMI in the UK study.…”
Section: International Journal Of Obesitysupporting
confidence: 66%
“…Thus, part of the genetic effect found in the previous studies may be mixed with environmental factors. These findings, when found more widely, would help reconcile why the very large genome-wide studies are unable to account for more than about 1% of the variance in BMI, [36][37][38] whereas family studies find evidence for substantial heritability even when common environmental effects are allowed for.…”
Section: Possible Sources Of Bias In Adoption Studiesmentioning
confidence: 88%
“…[15][16][17][18][19][20][21][22][23] As these studies have a cross-sectional design, it is not possible to examine the effect of a SNP on development of a trait. We suggest that rs1042522 has a role in the development of DBP and waist circumference during ageing and therefore, a SNP effect alone will be less informative compared with a SNP*time interaction in this case.…”
Section: Discussionmentioning
confidence: 99%
“…A number of genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) in the chromosome 6 region that includes ELOVL2 to be strongly associated with plasma fatty acid proportions (Aulchenko et al 2009;Sabatti et al 2009;Tanaka et al 2009;Illig et al 2010). A subsequent meta-analysis confirmed a number of minor allele associations with higher EPA and DPA and lower DHA proportions (Lemaitre et al 2011).…”
Section: Introductionmentioning
confidence: 99%